STUDY ON SURVIVABILITY OF NEWLY HATCHED LARVAE OF TWO SPECIES OF PEPPERMINT SHRIMP FED WITH DIFFERENT COMBINATIONS AND DENSITIES OF LIVE FOODS - Indra Pratama; Hatim Albasri (Indonesian Aquaculture Journal, 2019)
This study was aimed to evaluate different types and combinations of live foods in relation to the survivability of newly hatched Lysmata vittata and Lysmata intermedia larvae. The experiment consisted of three trials (different species, combinations, and densities of live foods) arranged in a completely randomized design. The first and second trials were subjected to L. vittata with three treatments for each trial (1A, 1B, 1C for trial-1; 1D, 1E, 1F for trial-2). The third trial consisted of two treatments (2A and 2B) tested on L. intermedia. Each treatment had three replicates. The results showed that the survival rates were low in all treatments. However, each treatment showed a significant effect (P<0.05) on the average survival rate of L. vittata and L. intermedia larvae. In the first trial, treatment 1C was the only one that had survived larvae after day 35 with 4.44% of final average survival rate (FASR). Four of the larvae reached the post-larval stage. In the second trial, treatment 1F showed a better condition than the other treatments with 5.56% FASR. Nevertheless, no larvae in the second trial had transformed to post-larval stage before the experiment ended at day 46. In the third trial, no larvae survived to reach the post-larval stage. In spite of this, treatment 2B had better daily average survival rate (DASR) than treatment 2A. This research concludes that the use of copepods as live food at an early larval stage and Artemia at a later stage is relatively more effective to improve the survival rate of peppermint shrimp larvae.